Potential and investment attractiveness of improved forestry projects under increasing climatic challenges - S. S. Morkovina; S. S. Sheshnitzan; A. V. Ivanova; N. V. Yakovenko; N. K. Pryadilina (Юг России: экология, развитие, 2024)
The aim is to justify the potential and provide an assessment of the effectiveness of investing in forest climate projects for improved forestry.A systematic approach was used for a comprehensive, structured and dynamic study of the potential of project activities (forest‐climatic projects) to improve forest productivity. The investment efficiency of forest‐climatic projects on improved forestry is determined taking into account the life cycle of project solutions. To conduct an express assessment of investment attractiveness of forest‐climatic projects, the coefficient characterizing the efficiency of investment for the produce of carbon units was used.It has been revealed that the regions of the Northwestern, Ural and Siberian Federal Districts have the greatest potential of areas of plots (over 2 million ha) for the realization of forest‐climatic projects on improved forestry. It has been shown that for the implementation of forest‐climatic projects on improved forestry in the conditions of the Central forest‐steppe per 1 ha investments of up to 100 thousand rubles are required. For climatic projects on improved forestry, the minimum investment per unit area will be from 97–111 thousand rubles per 1 ha, taking into account the life cycle of the project.The actual practice‐oriented task in the field of forestry has been solved. It consisted in substantiating the investment attractiveness of natural solutions aimed at increasing the carbon depositing functions of forest ecosystems. Calculated potential of areas for the implementation of forest‐climatic projects on improved forestry is an important tool for territorial planning and ensuring sustainable development of regional systems.